Circadian-like patterns in electrochemical skin conductance measured from home-based devices: a retrospective study - Vittrant, Benjamin; Courrier, Violaine; Yang, Rui-Yi; de Villèle, Paul; Tebeka, Samuel; Mauries, Sibylle; Geoffroy, Pierre A. (Frontiers in Neurology, 2023)
In this study, we investigated the potential of electrochemical skin conductance (ESC) measurements gathered from home-based devices to detect circadian-like patterns. We analyzed data from 43,284 individuals using the Withings Body Comp or Body Scan scales, which provide ESC measurements. Our results highlighted a circadian pattern of ESC values across different age groups and countries. Our findings suggest that home-based ESC measurements could be used to evaluate circadian rhythm disorders associated with neuropathies and contribute to a better understanding of their pathophysiology. However, further controlled studies are needed to confirm these results. This study highlights the potential of digital health devices to generate new scientific and medical knowledge.